2014
DOI: 10.1371/journal.pone.0084962
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of APP, ADAM10 and ADAM17 in the Denervated Mouse Dentate Gyrus

Abstract: The disintegrin and metalloproteinases ADAM10 and ADAM17 are regarded as the most important α-secretases involved in the physiological processing of amyloid precursor protein (APP) in brain. Since it has been suggested that processing of APP by α-secretases could be involved in the reorganization of the brain following injury, we studied mRNA expression of the two α-secretases Adam10 and Adam17, the ß-secretase Bace1, and the App-gene family (App, Aplp1, Aplp2) in the dentate gyrus of the mouse following entor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 72 publications
(94 reference statements)
0
32
0
Order By: Relevance
“…They concluded that in vivo APP levels in astrocytes may be too low for detection even under reactive conditions (Guo et al, 2012). In our own investigations, in which we used entorhinal cortex lesions (Lynch et al, 1978; Steward, 1994; Deller and Frotscher, 1997) to denervate the DG, we also failed to see an increase in App mRNA in the denervated outer molecular layer (Del Turco et al, 2014). In this layer, reactive glia are particularly abundant (Deller et al, 2000, 2007; Del Turco et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…They concluded that in vivo APP levels in astrocytes may be too low for detection even under reactive conditions (Guo et al, 2012). In our own investigations, in which we used entorhinal cortex lesions (Lynch et al, 1978; Steward, 1994; Deller and Frotscher, 1997) to denervate the DG, we also failed to see an increase in App mRNA in the denervated outer molecular layer (Del Turco et al, 2014). In this layer, reactive glia are particularly abundant (Deller et al, 2000, 2007; Del Turco et al, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…In our own investigations, in which we used entorhinal cortex lesions (Lynch et al, 1978; Steward, 1994; Deller and Frotscher, 1997) to denervate the DG, we also failed to see an increase in App mRNA in the denervated outer molecular layer (Del Turco et al, 2014). In this layer, reactive glia are particularly abundant (Deller et al, 2000, 2007; Del Turco et al, 2014). Although these two reports cannot rule out the possibility that under some other conditions APP is expressed in vivo by glial cells, they certainly suggest that glial APP is not the primary source of APP in the intact or injured brain.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…For example, immunolabelling has revealed increased expression of ADAM10 and ADAM17 associated with reactive astrocytes in murine dentate gyrus [32]. ADAM10 has also been found to be increased in immunohistochemical studies of HIV encephalitis clinical samples in both astrocytes and neurons [33].…”
Section: Introductionmentioning
confidence: 99%